Acknowledgement of manuscript reviewers 2015. Issue 1 (December 2016) - Crofts, Nick; Lawson, Euan
Contributing reviewers The editors ofHarm Reduction Journal would like to thank all our reviewers who have contributed to the journal in Volume 12 (2015).